Undoing the Collective Amnesia: A Brief Discussion of Feminism and Women Writers in Hungary - MacDonald, Agnes Vashegyi (Atlantis, 2010)
This paper expands on current studies that examine the history of Hungarian feminism while making links with the discourse of late nineteenth and early twentieth century women writers. Issues of suffrage, public health, prostitution, and the challenging of patriarchal ideologies and structures were key subjects for feminists and women writers in Hungary.